The Influence of Principal’s Participatory Leadership and School’s Culture on Teacher’s Job Satisfaction - Efni, Widya; Ahyani, Nur; Fitria, Happy (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine whether there is an influence between the principal’s participatory leadership and school culture on the job satisfaction of teachers of SMA Negeri in Prabumulih Timur District. The population of this study were teachers at State Senior High Schools in East Prabumulih District, namely State Senior High School 3 and State Senior High School 7 Prabumulih, totaling 167 teachers and the research sample was taken using the Slovin formula as many as 96 teachers. This type of research uses quantitative research with correlation and quantitative descriptive research methods, while the sampling is done by random sampling. the research instrument uses a questionnaire or questionnaire that has been tested for validity and tested for reliability. The results of the research hypothesis using the regression test, namely simple linear regression and multiple linear regression using SPSS indicate that there is a significant influence between the principal’s participatory leadership on teacher job satisfaction, school culture on teacher job satisfaction in SMA Neger in Prabumulih Timur District with a significant value of p <0 .05, namely 0.000, it can be concluded if the alternative hypothesis is accepted. Then between the principal’s participatory leadership and school culture on the job satisfaction of public high school teachers in East Prabumulih District is at a level of p <0.05 which is equal to 0.000, so the alternative hypothesis is accepted which means that there is a significant influence simultaneously between the principal’s participatory leadership and culture schools on the job satisfaction of public high school teachers in East Prabumulih District.